2014
DOI: 10.7763/ijbbb.2014.v4.344
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urinary Cadmium on Liver Function and Erythrocytes Cell Count in Pregnancy

Abstract: Abstract-Cadmium (Cd) is a heavy metal, which is used in many industries and was confirmed as an environmental toxin and mainly effects haematological system and liver. Previous studies showed that Cd induced damage of the liver and influenced erythrocytes. The effect of Cd in haematological system and liver function especially in pregant women has not been much studied. Thus our study aimed to evaluate the potential effect of cadmium exposure on erythrocytes and liver function in pregnant women by measuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Clinical studies have also confirmed the significance of hepatotoxicity induced by Cd, which is present in soil, water, food (dietary intake), and air (smoking and air pollution), and considered an important health concern [15,[29][30][31]. Other studies have also shown the positive correlation of serum Cd concentrations with liver enzyme levels (ALT, AST, and ALP) in Korean adults [32] and Indonesian pregnant women [33], which is consistent with this study. According to the evidence, the body has a limited capacity to Cd exposure, and the long-term exposure to Cd accumulates Cd and causes toxicity in several organs, such as liver and kidneys and impair their function [34][35][36], indicating the toxic effect of Cd in different organ systems [37].…”
Section: E Effects Of a Hirtifolium Extract On Hepatic Oxidativesupporting
confidence: 90%
“…Clinical studies have also confirmed the significance of hepatotoxicity induced by Cd, which is present in soil, water, food (dietary intake), and air (smoking and air pollution), and considered an important health concern [15,[29][30][31]. Other studies have also shown the positive correlation of serum Cd concentrations with liver enzyme levels (ALT, AST, and ALP) in Korean adults [32] and Indonesian pregnant women [33], which is consistent with this study. According to the evidence, the body has a limited capacity to Cd exposure, and the long-term exposure to Cd accumulates Cd and causes toxicity in several organs, such as liver and kidneys and impair their function [34][35][36], indicating the toxic effect of Cd in different organ systems [37].…”
Section: E Effects Of a Hirtifolium Extract On Hepatic Oxidativesupporting
confidence: 90%
“…Cadmium (Cd) is a widely but sparsely distributed element found in the earth's crust and is primarily association with zinc ore. Cd is a common by product of processing zincbearing ore [1][2] . It has long been recognized as one of the most toxic elements because its tend to have a slow elimination rate and its half-life in the human body ranges between 10-30 years [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%